Broadband Waveguide Feed for Parabolic Reflectors - P. Bhushan Mital (Active and Passive Electronic Components)
The broadband requirement in microwave systems has necessitated attention on components that can operate over frequency ranges far broader than those of standard rectangular waveguides. This paper describes the design and development of an ridged horn to match the waveguide impedance to freespace impedance so that the horn could be used as a feed for an offset-fed parabolic reflector over a wide band of frequencies, i.e., C and X bands (4.2 to 10.2 GHZ). In the present case, a five stepped chebyshev transformer has been used. Complete design required for horn feed as well for the ridged waveguide components necessary for testing has been carried out. The results obtained are quite encouraging. Good agreement is found between the measured results and theoretical values.